Сільський зелений туризм як запорука розвитку сільських територій - Пасєка, С. Р.; Демко, Валентина Сергіївна; Демко, Валентина Сергеевна; Demko, Valentyna (My University, 2017)
UK: У статті розглянуто стан і розвиток сільського зеленого туризму в Запорізькій області, як раціонального заходу диверсифікації підприємницької діяльності сільських територій та впровадження альтернативного виду зайнятості сільського населення. Наведено основні умови і фактори для його покращення. EN: Rural green tourism is not so much profitable and commercial activity as a socioeconomic phenomenon, which gives a chance to revive the rural economy, to pre-serve its traditional values and rural communities. In most countries, it is consid-ered as an integral part of the program of integrated socio-economic development of the village, since it allows to solving the problems of unemployment, replen-ishing the local budget, marketing agricultural products, infrastructure develop-ment, etc. The development of rural green tourism in the Zaporizhzhya region has own specificity, due to the complex influence of various factors - recreational, historical, geographical, ethnographic, cultural, economic, social and others, and it has enormous preconditions for further development. It, in its turn will be promoting the development of rural territories of the region and tourism sector in Ukraine.
Rural green tourism as the pledge of agricultural territories development
Keywords: сільський зелений туризм; суб’єкти аграрного сектору; диференціація; операційна діяльність; сільські території; агротуристичний продукт; підприємницька діяльність; агросадиба; rural green tourism; subjects of the agrarian sector; differentiation; operational activity; rural territories; agritourism product; entrepreneurial activity; agro farmstead